Combat Heart Problems with magic medicinal plant arjun (Terminalia arjuna) - Singh, Ghan Shyam (Indian Farming, 2015)
Terminalia arjuna is a unique herbal remedy for various heart problems. Due to its cardio protective role, it is being used in Ayurveda since 2500 BC and has remarkable cardio protective, heart muscle strengthening properties. Numerous Ayurvedic medicines prepared from arjun tree are available in market also. The medicinal property described here give fundamental idea Therefore, it is advisable to take various medicines only after proper medical advice from a recognized Ayurvedic physician.